The slippage of the driving wheels of a tractor in a cultivated soil and stubble - Janulevičius, Algirdas; Giedra, Kazimieras (Transport, 2009)
The article analyses the relation between the slippage of driving wheels and the traction characteristics of a tractor. The indicators for estimating wheel slippage are a coefficient of tractor weight force utilization for driving wheel grip and a coefficient of the ratio of trailer and tractor mass. The dependencies of wheel slippage on the weight utilization coefficient of tractors and the ratio of trailer and tractor mass are overviewed. The presented and carried out analysis of the equations of weight utilization coefficient ϕ g determined its dependencies on rolling resistance coefficients f of a means of transport, working speed v and acceleration a on the mass ratio of a trailer and tractor mp / mt . The results of experimental research on acceleration and constant speed regimes in a cultivated soil and stubble are presented. The dependencies of slippage on the ratio of trailer and tractor mass and the weight utilisation coefficient of a tractor and trailer are viewed. First published online: 27 Oct 2010